The impact of cold on the respiratory tract and its consequences to respiratory health - D’Amato, Maria; Molino, Antonio; Calabrese, Giovanna; Cecchi, Lorenzo; Annesi-Maesano, Isabella; D’Amato, Gennaro (Clinical and translational allergy, 2018)
The increasing use, and sometimes the abuse, particularly in industrialized countries of air conditioning at home, in car, hotel and shopping centres has highlighted new emerging public health issues, resulting from exposure of the airways to cool air or, more properly, resulting from sudden temperature changes. This is part of a wider problem, relating to air quality in indoor environment, such as homes or offices, where people spend more than 90% of their time. In particular, if indoor exposure occurs quickly and without any gradual adaptation to a temperature 2°–3° lower than the external temperature and especially with a 5° difference (avoiding indoor temperature below 24°) and an humidity between 40 and 60%, there is a risk of negative consequences on the respiratory tract and the patient risks to be in a clinical condition characterized by an exacerbation of the respiratory symptoms of his chronic respiratory disease (asthma and COPD) within a few hours or days. Surprisingly, these effects of cold climate remain out of the focus of the media unless spells of unusually cold weather sweep through a local area or unstable weather conditions associated with extremely cold periods of increasing frequency and duration. Moreover, the energy consumed by air conditioning induces an increase of CO 2 in atmosphere with increase of global warming. There is a need to better define the consequences of repeated exposure to cold air and the mechanisms by which such exposure could modify airway function and affect the outcomes of patients with pre-existing airway disease. This could help to promote adequate policy and public health actions to face the incoming challenges induced by climate change and global warming.